The chloroplast genome and chloroplast gene expression - Howe, Christopher (Henry Stewart Talks, 2007)
Early evidence for a chloroplast genome, Organization of the chloroplast genome in plants and algae, Gene content, Transcription, Roles of bacterial and phage-type RNA polymerases, Post-transcriptional modification, Splicing, editing and RNA turnover, Translation, Genome evolution, Transfer of genes to the nucleus
Archived at 2022/05/31